Voice Disorders: Etiology and Diagnosis - Martins, Regina Helena Garcia [UNESP]; do Amaral, Henrique Abrantes [UNESP]; Tavares, Elaine Lara Mendes [UNESP]; Martins, Maira Garcia [UNESP]; Gonçalves, Tatiana Maria [UNESP]; Dias, Norimar Hernandes [UNESP] (Elsevier, 2016)
Objectives Voice disorders affect adults and children and have different causes in different age groups. The aim of the study is to present the etiology and diagnosis dysphonia in a large population of patients with this voice disorder.for dysphonia of a large population of dysphonic patients. Methods We evaluated 2019 patients with dysphonia who attended the Voice Disease ambulatories of a university hospital. Parameters assessed were age, gender, profession, associated symptoms, smoking, and videolaryngoscopy diagnoses. Results Of the 2019 patients with dysphonia who were included in this study, 786 were male (38.93%) and 1233 were female (61.07). The age groups were as follows: 1–6 years (n = 100); 7–12 years (n = 187); 13–18 years (n = 92); 19–39 years (n = 494); 41–60 years (n = 811); and >60 years (n = 335). Symptoms associated with dysphonia were vocal overuse (n = 677), gastroesophageal symptoms (n = 535), and nasosinusal symptoms (n = 497). The predominant professions of the patients were domestic workers, students, and teachers. Smoking was reported by 13.6% patients. With regard to the etiology of dysphonia, in children (1–18 years old), nodules (n = 225; 59.3%), cysts (n = 39; 10.3%), and acute laryngitis (n = 26; 6.8%) prevailed. In adults (19–60 years old), functional dysphonia (n = 268; 20.5%), acid laryngitis (n = 164; 12.5%), and vocal polyps (n = 156; 12%) predominated. In patients older than 60 years, presbyphonia (n = 89; 26.5%), functional dysphonia (n = 59; 17.6%), and Reinke's edema (n = 48; 14%) predominated. Conclusions In this population of 2019 patients with dysphonia, adults and women were predominant. Dysphonia had different etiologies in the age groups studied. Nodules and cysts were predominant in children, functional dysphonia and reflux in adults, and presbyphonia and Reinke's edema in the elderly.
Keywords: Dysphonia; Epidemiology; Etiology; Hoarseness; Voice disorders